Structural and functional integrity of Sulla carnosa photosynthetic apparatus under iron deficiency conditions. (11th February 2018) - Elkhouni, A.; Rabhi, M.; Ivanov, A. G.; Krol, M.; Zorrig, W.; Smaoui, A.; Abdelly, C.; Huner, N. P. A.
Abstract: The abundance of calcareous soils makes bicarbonate‐induced iron (Fe) deficiency a major problem for plant growth and crop yield. Therefore, Fe‐efficient plants may constitute a solution for use on calcareous soils. We investigated the ability of the forage legume Sulla carnosa (Desf.) to maintain integrity of its photosynthetic apparatus under Fe deficiency conditions. Three treatments were applied: control, direct Fe deficiency and bicarbonate‐induced Fe deficiency. At harvest, all organs of deficient plants showed severe growth inhibition, the effect being less pronounced under indirect Fe deficiency. Pigment analysis of fully expanded leaves revealed a reduction in concentrations of chlorophyll a, chlorophyll b and carotenoids under Fe deficiency. Electron transport rate, maximum and effective quantum yield of photosystem II (PSII), photochemical quenching (qP), non‐photochemical quenching (qN) as well as P700 activity also decreased significantly in plants exposed to direct Fe deficiency, while qN was not affected. The effects of indirect Fe deficiency on the same parameters were less pronounced in bicarbonate‐treated plants. The relative abundances of thylakoid proteins related to PSI (PsaA, Lhca1, Lhca2) and PSII (PsbA, Lhcb1) were also more affected under direct than indirect Fe deficiency. We conclude that S. carnosa can maintain the integrity of its photosynthetic apparatus under bicarbonate‐induced Fe deficiency, preventing harmful effects to both photosystems under direct Fe deficiency. This suggests a high capacity of this species not only to take up Fe in the presence of bicarbonate (HCO3 − ) but also to preferentially translocate absorbed Fe towards leaves and prevent its inactivation.